YAUMIDDIN DALAM PERSPEKTIF HERMENEUTIKA EMILIO BETTI - Adinugraha, Hendri Hermawan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
This paper seeks to interpret the word “yaumiddin” in QS. Al-Fatihah: 4 from the perspective of Emilio Betti hermeneutic theory. This paper uses lierature research approach which sourced from books, journals, and other literature that still have relevance to this topic. The results of study showed that in a perspective of Betti the text closely related to the activities of interpretation of the meaning contained in the text. Meaning always refers to the objectivity of the interpreter thought. Therefore, the interpretation of the text should be the movement of interpretation that involves linguistic aspects, historical background and introduction to the author together. Betti hermeneutical method is more emphasis on the reconstruction of the intellectual horizons of meaning armed interpreter (subject) using a model of reproductive interpretation. Based on Betti theory that text “yaumiddin” on QS. Al-Fatihah: 4 means the day he blew the trumpet, where the day that no one can defend someone else, so the day was named as well as the decisions and the Day of Judgment by Allah SWT.